Intraneuronal Abeta, non-amyloid aggregates and neurodegeneration in a Drosophila model of Alzheimer's disease. - Crowther, D.C.; Kinghorn, K.J.; Miranda, E.; Page, R.; Curry, J.A.; Duthie, F.A.I.; Gubb, D.C.; Lomas, D.A. (Neuroscience, 2005)
We have developed models of Alzheimer's disease in Drosophila melanogaster by expressing the Abeta peptides that accumulate in human disease. Expression of wild-type and Arctic mutant (Glu22Gly) Abeta(1-42) peptides in Drosophila neural tissue results in intracellular Abeta accumulation followed by non-amyloid aggregates that resemble diffuse plaques. These histological changes are associated with progressive locomotor deficits and vacuolation of the brain and premature death of the flies. The severity of the neurodegeneration is proportional to the propensity of the expressed Abeta peptide to form oligomers. The fly phenotype is rescued by treatment with Congo Red that reduces Abeta aggregation in vitro. Our model demonstrates that intracellular accumulation and non-amyloid aggregates of Abeta are sufficient to cause the neurodegeneration of Alzheimer's disease. Moreover it provides a platform to dissect the pathways of neurodegeneration in Alzheimer's disease and to develop novel therapeutic interventions.